Experimental investigation into the use of emergency spray on suppression of battery thermal runaway. (June 2021) - Huang, Yuqi; Wu, Yinghao; Liu, Binghe
Highlights: The spray cooling solution is used to suppress battery thermal runaway. Both spray triggering temperature and spray duration affect suppression results. Select appropriate triggering temperature can save spray cost and ensure safety. Formulas are conducted to calculate necessary spray duration with mass flow rate. Abstract: The thermal safety of lithium-ion batteries limits the development of electric vehicles. When the battery heat generation rate exceeds the critical cooling rate of the battery thermal management system, thermal runaway will occur. This article uses spray as an emergency cooling method to suppress battery thermal runaway, which can inhibit the battery heating process when the thermal management system cannot meet the heat dissipation requirements, and ensure thermal safety across the entire temperature range. In this paper, spray is applied to the cooling of battery thermal runaway, and a series of experiments are carried out to study the inhibitory effect of spray cooling on the battery. This experiment explored the influence of spray trigger temperature ( T e ) and spray duration ( t s ) on the suppression effect of thermal runaway. In order to achieve a lightweight and economical spray system, whilst ensuring an efficient cooling performance, we tried to analyze the relationship between T e and t s, hoping to quantitatively control spray flow and use the smallest spray flow to achieve suppression.This research provides meaningful results for the application of spray cooling in suppressing battery thermal runaway.